Nucleosynthetic yields from neutron stars accreting in binary common envelopes. Issue 1 (6th February 2019) - Keegans, J; Fryer, C L; Jones, S W; Côté, B; Belczynski, K; Herwig, F; Pignatari, M; Laird, A M; Diget, C Aa
Abstract: Massive-star binaries can undergo a phase where one of the two stars expands during its advanced evolutionary stage as a giant and envelops its companion, ejecting the hydrogen envelope and tightening its orbit. Such a common envelope phase is required to tighten the binary orbit in the formation of many of the observed X-ray binaries and merging compact binary systems. In the formation scenario for neutron star binaries, the system might pass through a phase where a neutron star spirals into the envelope of its giant star companion. These phases lead to mass accretion on to the neutron star. Accretion on to these common-envelope-phase neutron stars can eject matter that has undergone burning near to the neutron star surface. This paper presents nucleosynthetic yields of this ejected matter, using population synthesis models to study the importance of these nucleosynthetic yields in a galactic chemical evolution context. Depending on the extreme conditions in temperature and density found in the accreted material, both proton-rich and neutron-rich nucleosynthesis can be obtained, with efficient production of neutron-rich isotopes of low Z material at the most extreme conditions, and proton-rich isotopes, again at low Z, in lower density models. Final yields are found to be extremely sensitive to the physical modelling of the accretion phase. We show that neutron stars accreting in binary common envelopes might be a new relevant site for galactic chemical evolution, and therefore more comprehensive studies are needed to better constrain nucleosynthesis in these objects.